Designing Pragmatic Formula for Local English Textbooks Development - Nurdiana Nurdiana (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Language teaching materials play a significant role in language learning as it provides input for learners. The language input should contain all of the aspects of communicative competence, one of which is pragmatic competence. This is because pragmatics deals with language use in context. Learning a language is not merely about learning how to make grammatically correct sentences, but it is also about how to use the sentence appropriately. Thus, learners should be exposed to pragmatics to be able to use the language they learn in context. For this reason, this study aims to design a pragmatic formula for English language teaching materials (textbooks) development as previous studies on pragmatics on English language textbooks reported that many of them, particularly the local ones contain insufficient pragmatic knowledge. The present research employed a qualitative approach by referring to the earlier studies on pragmatics in language textbooks. Findings indicated that it was not an easy assignment to design pragmatic formula as it required a lot of observation of teaching materials and pragmatic judgment by a native speaker of American English. Keywords: pragmatics, language coursebooks, materials development